2014
DOI: 10.1186/1471-2474-15-87
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prevalence of calcaneal spurs in men & women: a random population from a trauma clinic

Abstract: BackgroundThis study reports the changing prevalence of ankle (Achilles and plantar) spurs with age, in order to comment on their significance to rheumatologists.Methods1080 lateral ankle radiographs from each of 9 (50 men and 50 women) age cohorts from 2 to 96 years old of patients attending a trauma clinic were examined and spurs classified as small or large.ResultsThe prevalence of both Achilles and plantar spurs in relation to the age categories and sex was variable. Overall, there was 38% of the populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 12 publications
5
38
2
2
Order By: Relevance
“…Plantar spur seems to be more common than spur occurring at the insertion of achilles. 9 It is evident from the study that patients under 30 years of age do not show any presence of calcaneal spurs which could explain the spur formation to be part of a degenerative process resulting in osteophyte formation appearing in the form of bony growth. Its prevalence among women could be correlated with footwear, obesity and pregnancy resulting in excessive compressive forces acting at the calcaneum over a period of time.…”
Section: Discussionmentioning
confidence: 76%
“…Plantar spur seems to be more common than spur occurring at the insertion of achilles. 9 It is evident from the study that patients under 30 years of age do not show any presence of calcaneal spurs which could explain the spur formation to be part of a degenerative process resulting in osteophyte formation appearing in the form of bony growth. Its prevalence among women could be correlated with footwear, obesity and pregnancy resulting in excessive compressive forces acting at the calcaneum over a period of time.…”
Section: Discussionmentioning
confidence: 76%
“…They proposed that this age‐dependent difference may be due to the altered foot biomechanics of wearing high‐heeled shoes (Toumi et al. ; Yung‐Hui & Wie‐Hsien, ).…”
Section: Associations With Pcsmentioning
confidence: 99%
“…In one study that broke the population down into nine age cohorts, PCS was reported to occur more commonly in women under 49 years of age than in men. They proposed that this age-dependent difference may be due to the altered foot biomechanics of wearing high-heeled shoes (Toumi et al 2014;Yung-Hui & Wie-Hsien, 2005).…”
Section: Pcs and Gendermentioning
confidence: 99%
“…An incidence rate varying between 11% and 46% was reported in the literature. 2 , 3 , 4 , 5 This rate increases in patients with advanced age, osteoarthritis and obesity. 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%